Clinical experience treating Paecilomyces lilacinus keratitis in four patients - Monden Y (Dove Medical Press, 2012)
Yu Monden,1 Minoru Sugita,1 Ryoji Yamakawa,1 Kazuko Nishimura,21Department of Ophthalmology, Kurume University School of Medicine, Kurume, Fukuoka, Japan; 2Medical Mycology Research Center, Chiba University and First Laboratories Co Ltd, Kawasaki, Kanagawa, JapanBackground: Paecilomyces lilacinus is a saprobic fungus that occasionally causes keratitis in infected patients. Voriconazole, a triazole antifungal agent, is often administered to treat P. lilacinus keratitis, because it is resistant to many antifungal agents. However, some patients may not require voriconazole. Here, we report our experience of treating this infection and compare outcomes between patients treated with or without voriconazole.Subjects: We retrospectively reviewed four cases of infectious keratitis caused by P. lilacinus and compared treatment course and outcomes among the four cases.Observations: P. lilacinus was isolated from corneal cultures in all four cases. Three cases developed corneal perforation and underwent keratoplasty. Voriconazole was given in two cases with severe and refractory infection. Both required long-term treatment despite the effectiveness of voriconazole. They also had a medical history of diabetes and corticosteroid therapy. In two cases that were not treated with voriconazole, the eye conditions improved with a short treatment period (2–3 weeks). Neither of these cases had a medical history of diabetes, nor had they used corticosteroids.Conclusion: Although voriconazole is the most useful antifungal agent for treating P. lilacinus keratitis, this infection can be resolved by other treatments. Voriconazole should be offered to patients with diabetes and/or prior corticosteroid use.Keywords: Paecilomyces lilacinus, voriconazole, diabetes, corticosteroids